Making new connections: Insights from primate parasite networks - Rushmore, J; Bisanzio, D; Gillespie, T (Elsevier, 2017)
Social interactions are important in everyday life for primates and many other group-living animals; however, these essential exchanges also provide opportunities for parasites to spread through social groups. Network analysis is a unique toolkit for studying pathogen transmission in a social context, and recent primate–parasite network studies shed light on linkages between behavior and infectious disease dynamics, providing insights for conservation and public health. We review existing literature on primate–parasite networks, examining determinants of infection risk, issues of network scale and temporal dynamics, and applications for disease control. We also discuss analytical and conceptual gaps that should be addressed to improve our understanding of how individual and group-level factors affect infection risk, while highlighting interesting areas for future research.